2021
DOI: 10.1177/15245004211013333
|View full text |Cite
|
Sign up to set email alerts
|

Influencing the Intention to Adopt Anti-Littering Behavior: An Approach With Modified TPB Model

Abstract: Background: Littering has been identified as a major issue in India that has negative impacts on the environment as well as public health. Focus of the article: Guided by the Theory of Planned Behavior, this empirical study determines the influence of three major concepts namely attitude, subjective norms, and self-efficacy on the intention to adopt anti-littering behavior. Research Hypotheses: The hypotheses stipulate that attitude, subjective norms, and self-efficacy have a significant influence on the inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 63 publications
5
20
0
Order By: Relevance
“…What is significant from the results of Ojedokun and Balogun 4 and Singh and Kaur 47 is that the socially constructed belief of a person in themself and their abilities will facilitate the person to take responsibility for their own behaviour and actions, including towards the environment. 46 Theme 2: Those who litter have no respect and care for self, others and the environment This theme confirms the results by Ojedokun and Balogun 4 and Singh and Kaur 47 (mentioned in the previous discussion) that people with a disregard for self, others and the environment will take less responsibility for their own environment -the responsibility will be assigned to other persons or institutions. In this study, participants highlighted the following traits as reasons for littering: 'They have no self-respect for themselves and other people'; 'They do not care about the environment'; 'They do not care about the community.…”
Section: Theme 1: Value Systems and Personality Traitssupporting
confidence: 69%
“…What is significant from the results of Ojedokun and Balogun 4 and Singh and Kaur 47 is that the socially constructed belief of a person in themself and their abilities will facilitate the person to take responsibility for their own behaviour and actions, including towards the environment. 46 Theme 2: Those who litter have no respect and care for self, others and the environment This theme confirms the results by Ojedokun and Balogun 4 and Singh and Kaur 47 (mentioned in the previous discussion) that people with a disregard for self, others and the environment will take less responsibility for their own environment -the responsibility will be assigned to other persons or institutions. In this study, participants highlighted the following traits as reasons for littering: 'They have no self-respect for themselves and other people'; 'They do not care about the environment'; 'They do not care about the community.…”
Section: Theme 1: Value Systems and Personality Traitssupporting
confidence: 69%
“…First, the results revealed that both the TPB model and NAM model displayed explanatory capacity on hikers' PEB in Wuyishan National Park in China. Scholars from a variety of disciplines have regularly evaluated the suitability of utilizing TPB or NAM models to explain PEB (Han, 2015(Han, , 2021Alzubaidi et al, 2021;Aziz et al, 2021;Singh and Kaur, 2021;Cao et al, 2022;Kang, 2022;Long et al, 2022;Song et al, 2022;Zheng et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…To achieve a more sustainable society, encouraging hikers to participate in a variety of PEB can subsequently increase favorable environmental outcomes and lessen the severity of global environmental challenges (Goh, 2020;Udall et al, 2020;Choi and Kim, 2021;Esfandiar et al, 2022). Previous studies about PEB have generally focused on personal factors regarding tourists, such as their attitude (ATT), subjective norm (SN), and perceived behavioral control (PBC) mechanisms as well as the environmental behavioral intention of theory of planned behavior (TPB) (De Leeuw et al, 2015;Han, 2020;Meng et al, 2020;Yuriev et al, 2020;Alzubaidi et al, 2021;Aziz et al, 2021;Fenitra et al, 2021;Panwanitdumrong and Chen, 2021;Singh and Kaur, 2021;Zhang et al, 2021;Loureiro et al, 2022;Zheng et al, 2022); awareness of consequences (AC), ascription of responsibility (AR), and personal norm (PN) of the norm activation theory (NAM) (Meng et al, 2020;Alzaidi and Iyanna, 2021;Bai and Zhang, 2021;O'Connor and Assaker, 2021;Han et al, 2021;Cao et al, 2022;Jeon et al, 2022;Kang, 2022;Long et al, 2022;Loureiro et al, 2022;Song et al, 2022;Zhang et al, 2022). However, there are many influencing factors of personal PEB, and there are complex interrelationships, there are both have direct and indirect effects (Han, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the omission of SE and OE is a limitation because previous research found them it to be influential (e.g. Joanes, 2019;Nordlund et al, 2018Nordlund et al, , 2016Singh & Kaur, 2021;Steg & De Groot, 2010). However, our decision to focus on AC and AR was made not only because of limitations of time and the complexity of this research project, but more importantly to meet the pioneering character of the work.…”
Section: Limitations and Future Researchmentioning
confidence: 99%